Effect of Electrical Stimulation on Ocular Cells: A Means for Improving Ocular Tissue Engineering and Treatments of Eye Diseases - Fatemeh Sanie-Jahromi (Hindawi Limited, 2021)
Tissue engineering is biomedical engineering that uses suitable biochemical and physicochemical factors to assemble functional constructs that restore or improve damaged tissues. Recently, cell therapies as a subset of tissue engineering have been very promising in the treatment of ocular diseases. One of the most important biophysical factors to make this happen is noninvasive electrical stimulation (ES) to target ocular cells that may preserve vision in multiple retinal and optic nerve diseases. The science of cellular and biophysical interactions is very exciting in regenerative medicine now. Although the exact effect of ES on cells is unknown, multiple mechanisms are considered to underlie the effects of ES, including increased production of neurotrophic agents, improved cell migration, and inhibition of proinflammatory cytokines and cellular apoptosis. In this review, we highlighted the effects of ES on ocular cells, especially on the corneal, retinal, and optic nerve cells. Initially, we summarized the current literature on the in vitro and in vivo effects of ES on ocular cells and then we provided the clinical studies describing the effect of ES on ocular complications. For each area, we used some of the most impactful articles to show the important concepts and results that advanced the state of these interactions. We conclude with reflections on emerging new areas and perspectives for future development in this field.